A multidimensional measure of managers' contextual and task performance. Issue 2 (7th March 2016) - Hosie, Peter; Nankervis, Alan
Abstract : Purpose: – The purpose of this paper it to report the findings of an empirical study into managers' job performance. A new measure was developed from the literature to test and establish the multidimensional structure of managers' contextual and task performance. Design/methodology/approach: – Field ratings by executives explicitly and simultaneously measured both managers' contextual and task performance. A cross-sectional questionnaire was administered to a variety of public and third sector managers from a range of private, public and third sector occupations residing in (Western) Australia. A purposive sample yielded a response rate of 32 percent. Factor analysis was used to determine the items that constitute executives' perceptions of managers' performance using downward appraisal (i.e. by the person to whom a manager reports). Findings: – The construct "managers' job performance" was found to be multidimensional; consisting of four distinct contextual factors (Following, Persisting, Helping, Endorsing) and a further four distinct task factors (Delegating, Monitoring, Technical, Influencing). Originality/value: – Performance appraisals of managers represent new items and factors that more accurately reflect the nature of the broader roles undertaken by managers, including transformative and ethical leadership. Findings from this study assist in establishing the structure for the subsequent appraisal of managers' contextual and task performance. Future researchers could test the applicability and replicability of this new instrument in more diverse industry contexts using confirmatory statistical analysis.